Laser-induced plasmas and applications - Radziemski, Leon J.; Cremers, David A. (Optical engineering (Marcel Dekker, Inc.), 1989)
Providing an interdisciplinary approach to plasma engineering and techniques, the book contains a timely examination of the physics of laser-induced breakdown.